SISTEM INFORMASI KEPEGAWAIAN PADA BADAN KEUANGAN DAN ASET DAERAH SUMATERA UTARA BERBASIS WEBSITE - M. Dio Aryadinata Panjaitan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to design and develop a website-based personnel information system at the North Sumatra Regional Finance and Asset Agency to improve the efficiency and effectiveness of personnel data management. This information system is designed to overcome various problems that often arise in manual data management, such as data duplication, delays in information processing, and difficulty in accessing fast and accurate data. The method used in this waterfall method research includes needs analysis, system design, development, and system testing. The resulting system has main features, namely management of employee personal data, work history, absence, performance assessment, and career development information. This website-based system allows related parties to access and manage personnel data in real-time, increasing ease in monitoring performance and personnel administration processes. The test results show that this system is able to improve the efficiency of personnel data management and minimize errors that occur in manual data processing. The implementation of this website-based personnel information system is expected to support the improvement of the performance of the North Sumatra Regional Finance and Asset Agency as a whole.